A STUDY ON TALENT MANAGEMENT ON JOB SATISFACTION AT ASHOK LEYLAND SHILPA WADHWA - SHILPA WADHWA (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Talent management is the practice of locating, retaining, and fostering the growth of the most talented employees available today. Talented employees benefit the business in a number of ways, including increased market value, high customer satisfaction, exceptional service, high revenue yield, low cost, and high productivity. Despite the benefits of talent management, the larger challenge is keeping these smart individuals given the harsh business environment that offers new possibilities to employees. The fact that relatively few firms put a major focus on talent management and their leadership structure when it comes to organizational and human resource management must also be emphasized. The corporation invests in new technologies, operating systems, and software planning even though the ultimate success of the business relies on having talented personnel, but they lack talent management abilities. The research's challenge is to evaluate employee happiness and talent management using a case study of a few selected banks in Lagos, despite the fact that modern companies are aware that their success depends on their capacity to inspire talented workers. Talent management and employee job satisfaction.